STRATEGI DAKWAH JAMAAH DZIKIR TOMBO NOTO ATI DESA KAWAK KABUPATEN JEPARA - Muhammad Lukman Ihsanuddin (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2016)
The uniqueness of the da'wah mission strategy Dzikir Tombo Noto Ati Kawak, Pakis Aji, Jepara stimulate the author to conduct a study. With qualitative research that relies on observation data, interviews and documentation, the author seeks to explore the main strategy in the indictment conducted by KH. Sirojuddin. The results of this study are 1) the implementation of the teachings of Dzikir Tombo Noto Ati is one of the da'wah activities that exist in the Village Kawak Pakis Aji District Jepara. In the routine activities, held every Friday night at 21:00 to 01:00 in the morning. Before dhikr and do'a are performed together, it usually begins with the yellow book of yellow first; 2) the approach used in pilgrims Tombo Noto Ati dzikir is through a socio-economic approach (approach with partners) and social psychology (approach from the psychological side); 3) dhikr Jama'ah use two strategy tawsi'ah strategy (addition of the number of Muslims) and tarqiyah (improvement of the quality of Muslims); 4) Assembly Jamaah Dzikir Tombo Noto Ati has several factors that support it, among others, strategic location, material in accordance with the conditions of Jamaah, and a conducive environment. While the factors that hampered the implementation of this activities, which is, among other times, the implementation time is felt less precise with the condition of citizens, weather, facilities are still minimal, and still at least Kawak villagers who follow this activities and more dominated by members outside Kawak Village.